COVID-19 and the changing employee experience - Aitken-Fox, Eileen; Coffey, Jane; Dayaram, Kantha; Fitzgerald, Scott; Gupta, Chahat; McKenna, Stephen; Tian, Amy (London School of Economics and Political Science, 2020)
To find the way forward, organisations need to engage employees in co-creating quality jobs